Corruption, environmental sustainability and economic performance in emerging economies: Evidence from Nigeria - Nkemdilim Iheanachor; Chris Ike Ogbechie; Azuka Elvis Ozegbe (International Journal of Management, Economics and Social Sciences (IJMESS), 2023)
This study was aimed at examining the linkages between corruption, environmental sustainability, and economic performance. It was motivated by the quest to test the validity of the Environmental Kuznets Curve (EKC) hypothesis in Nigerian. The EKC hypothesis explains the nexus between economic activities and environmental degradation. Therefore, this current study investigated the interconnections between corruption, environmental sustainability and economic performance in Nigeria using the modern Autoregressive Distributed Lag Model (ARDL) approach for the period from 1981 to 2020. The study revealed that corruption has negative and statistically significant effects on environmental quality and Nigeria's economic performance. In addition, the study showed that corruption has direct and indirect effects on environmental quality and asserted that corruption raises the level of C02 emissions and worsens the overall quality of environment, these empirical finding are in tandem with the postulation of the Environment Kuznets Curve (EKC) hypothesis. This shows that economic performance responds to the changes in corruption and carbon emission in the long-run in a negative and statistically significant manner. Therefore, the concerned regulatory agencies must be strengthened to firmly address violators of environmental regulations and enhance energy efficiency.
Keywords: C10; F43; H10; 330; Corruption; environmental degradation; economic performance; energy consumption; autoregressive distributed lag (ARDL)